Clinical features and prognosis of systemic lupus erythematosus complicated by active cytomegalovirus infection: a retrospective cohort study - Chen, Yan; Zhang, Lifan; Liu, Yuchen; Liu, Ye; Zhao, Lidan; Zhou, Baotong; Ruan, Guiren; Shi, Xiaochun; Liu, Xiaoqing (Frontiers in Immunology, 2024)
Objective The aim of this study was to investigate the clinical traits and consequences of systemic lupus erythematosus (SLE) complicated by active cytomegalovirus (CMV) infection. Methods This retrospective review involved the examination of medical records for patients diagnosed with SLE who had an active CMV infection at the time of their discharge from Peking Union Medical College Hospital between June 2016 and December 2022. The consistency between plasma CMV deoxyribonucleic acid (DNA) viral load and pp65 antigenemia was analyzed using the chi-square test. Related factors for CMV disease in SLE complicated by active CMV infection patients were analyzed by univariate analysis and multivariable stepwise logistic regression. Cox hazards regression analysis was used to determine predictors for all-cause mortality and CMV recurrence within 3 months. Results A total of 206 patients were enrolled in this study. Of the 123 patients who were detected with both plasma CMV DNA viral load and pp65 antigenemia within an interval not exceeding 72 h, the consistency between plasma CMV DNA viral load and pp65 antigenemia was not good (Kappa = −0.304, p < 0.001). Plasma CMV DNA viral load ≥ 1,600 copies/mL [odds ratio (OR) 4.411, 95% CI 1.871–10.402, p = 0.001], current glucocorticoids dose (equivalent to prednisolone) ≥60 mg/d (OR 2.155, 95% CI 1.071–4.334, p = 0.031), and elevated alanine transaminase (OR 3.409, 95% CI 1.563–7.435, p = 0.002) were significant clinical clues indicating CMV disease in SLE. Multivariable Cox hazards regression analysis showed that CMV organ involvement [hazard ratio (HR) 47.222, 95% CI 5.621–396.689, p < 0.001], SLE multi-system involvement (HR 1.794, 95% CI 1.029–3.128, p = 0.039), and elevated hypersensitive C-reactive protein (hsCRP) (HR 5.767, 95% CI 1.190–27.943, p = 0.030) were independent risk factors for 3-month all-cause mortality. CMV organ involvement (HR 3.404, 95% CI 1.074–10.793, p = 0.037) was an independent risk factor for CMV recurrence within 3 months. Conclusion In SLE patients, plasma CMV DNA viral load seemed to have a higher value in the diagnosis of CMV disease; patients with CMV organ involvement, SLE multi-system involvement, and elevated hsCRP might have a higher risk of 3-month all-cause mortality; and patients with CMV organ involvement might have a higher risk of CMV recurrence within 3 months.